The Academic Writing Performance of Novice EFL Student Teachers - Aziza Restu Febrianto (English Language and Education Spectrum, 2021)
Academic writing is an important skill that university students need to develop in order to be successful in their study and career after graduation. This article reports descriptive qualitative information about the performance of academic writing of novice EFL student teachers at an Indonesian private university. Thirteen students at the beginning semesters were involved in the study to constitute the sample. In collecting the data, IELTS writing test along with its assessment analysis and interviews were used. The study revealed that the mean of the students’ overall scores in the IELTS writing test is 5.0, which is equivalent to B1 level according to Common European Framework of Reference for Languages (CEFR). Learners at B1 level are considered as independent users of English or intermediate in using the language. In general, they can produce simple and coherent texts, but only on the topics they are familiar with. The study also unveiled the major issues and challenges faced by the students that include lack of vocabulary and knowledge of grammar in use as well as finding ideas and organizing them in communicativeparagraphs. Unfamiliarity about the test is also another issue hindering the students in writing. These findings resonate some related theories and other empirical studies especially on the issues of communicative competence. This article finally suggests a new upcoming paradigm in the teaching of academic writing particularly when preparing students to take the IELTS test for the sake of their education and career success